Heart Failure-Induced Diaphragm Myopathy - Ruiz Lima, Aline Regina [UNESP] (2014)
Background: Intracellular signaling pathways involved in skeletal myosin heavy chain (MyHC) isofornn alterations during heart failure (HF) are not completely understood. We tested the hypothesis that diaphragm expression of mitogen-activated protein kinases (MAPK) and myogenic regulatory factors is changed in rats with myocardial infarction (MI) induced HF. Methods: Six months after MI rats were subjected to transthoracic echocardiography. After euthanasia, infarcted rats were subdivided in MI/HF- group (with no HF evidence; n=10), and MI/HF+ (with right ventricular hypertrophy and lung congestion; n=10). Sham operated rats were used as controls (n=10). MyHC isofornns were analyzed by electrophoresis. Statistical analysis: ANOVA and Pearson correlation. Results: MI/HF- had left cardiac chambers dilation with systolic and diastolic left ventricular dysfunction. Cardiac injury was more intense in MI/HF+ than MI/HF-. MyHC I isoform percentage was higher in MI/HF+ than MI/HF-, and IIb isoform lower in MI/HF+ than Sham. Left atrial diameter-to-body weight ratio positively correlated with MyHC I (p=0.005) and negatively correlated with MyHC IIb (p=0.02). TNF-alpha serum concentration positively correlated with MyHC I isoform. Total and phosphorylated ERK was lower in MI/HF- and MI/HF+ than Sham. Phosphorylated JNK was lower in MI/HF- than Sham. JNK and p38 did not differ between groups. Expression of NF-kappa B and the myogenic regulatory factors MyoD, myogenin, and MRF4 was similar between groups. Conclusion: Diaphragm MyHC fast-to-slow shift is related to cardiac dysfunction severity and TNF-alpha serum levels in infarcted rats. Reduced ERK expression seems to participate in MyHC isofornn changes. Myogenic regulatory factors and NF-kappa B do not modulate diaphragm MyHC distribution during chronic HF. Copyright (C) 2014 S. Karger AG, Basel